Pharmacognostical and Phytochemical Evaluation of a New Anti-Hypertensive Ayurvedic Formulation [NIA/DG/2020/01] (International Journal of Ayurveda and Pharma Research, 2023)
Hypertension, also known as high or raised blood pressure, is a multifactorial disease with multiple causes and multiple treatments. The prevalence of hypertension in the urban Indian population was estimated to be 40.8% and in the rural population was 17.9%. Though there are multiple treatment of disease still it is challenge to manage this disease effectively with lower side effects as all available treatments are full of side effects and toxic effects. NIA/DG/2020/01 is a new anti-hypertensive Ayurvedic ghan formulation, containing Arjuna (Terminalia arjuna Roxb.), Ashwagandha (Withania somnifera Linn.), Jatamansi (Nordostachys jatamansi DC.), Shankhpushpi (Convolvulus pluricaulis Chois.), Punarnava (Boerhavia diffusa Linn.), Gojihwa (Onosma Bracteatum Wall.), Guduchi (Tinospora cordifolia Willd.), Mukta Shukti (Margarita) and Praval Pisti (Corrallium Rubrum). All these components are very well known for Hridya, Mootral, Rasayana, Pitta shamak effect and pharmacological actions like cardioprotective, anti-Hypertensive, antioxidant, antimicrobial, antifungal, Antidepressant or anxiolytic, anti-inflammatory, psycho-immunomodulatory effect and acetyl-cholinesterase inhibitory activity etc. Aim and Objective: To perform pharmacognostical, physio-chemical, phytochemical and chromatography evaluation of a new anti-hypertensive Ayurvedic formulation [NIA/DG/2020/01]. Material and Methods: This study involves pharmacognostical, physio-chemical, phytochemical and chromatography evaluation of a new anti-hypertensive Ayurvedic formulation [NIA/DG/2020/01] to ensure its purity, safety and quality. Observations and Results: All the findings of the pharmacognostical, physio-chemical, phytochemical and chromatography evaluation were within the standards of quality. Conclusion: The present sample of a new anti-hypertensive Ayurvedic formulation [NIA/DG/2020/01] was found to be rich in quality and was safe, pure and authentic.